Factors Associated with Effectiveness of NCD Clinic Plus Development in the Health Region 4, 2018 - รักเดช, วุฒิศักดิ์; จิตรภักดี, ขวัญใจ; คุ้มวงษ์, กมลวรรณ (Journal of Health Science of Thailand, 2021)
The objective of this research was to study development operations of NCD Clinic Plus, factors related to its effectiveness in the Public Health Region 4. The study samples were hospitals in the Public Health Region 4. The study tools were the forms to evaluate the 6 components of the NCD Clinic Plus assessment forms developed by the Bureau of Non-Communicable Diseases, Department of DiseaseControl, Ministry of Public Health. Data were analyzed using descriptive statistics; and the association was tested by using Chi-square and correlation analysis statistics. The results of this study indicated that the overall development of NCD Clinic Plus was at a very good level. The highest average scores were in the component 2 (information system) and 3 (system and process adjustment); and the lowest average was in the component 6 (community connection service). Development effectiveness was chosen based on the inspection and supervision related to NCD Clinic Plus in the fiscal year 2019. The factors related to the effectiveness of operations were as follows: the reduction of the percentage of new diabetic patients was associated with the efficiency of the element 2 (information system), element 4 (self-management support system), element 6 (community connection service) and the overall elements. The decline of new high blood pressure patients was associated with the efficiency of all elements (except element 5 - decision support system). Furthermore, the percentage of patients with good high blood pressure control was associated with the component 4 (self-management support system).